Influence of Sn- and Al- metal sources on post-synthesis modification of mesoporous SBA-15 molecular sieves - Shah, P; Ramaswamy, AV; Ramaswamy, V (3rd Conference of the Federation-of-European-Zeolite-Association, 2005)
Mesoporous silica SBA-15 has been incorporated with various amounts of Sn and Al by post synthesis grafting technique, which results in excellent structural integrity and enhanced acidity. Physico-chemical characterization was done by various spectroscopic methods to understand the chemical nature of incorporated Sn and Al. XRD and BET results show that the hexagonal structural of the SBA-15 is maintained during the grafting with no loss of long range structure ordering. (119)Sn NMR Spectrum shows the presence of Sri in essentially octahedral environment, while 27 Al MAS NMR results confirm that a large proportion of the Al is in tetrahedral position. The resulting Sn and Al-grafted materials possess considerable catalytic activity in the transesterification of diethylmalonate (medium acidity) and isopropylation of naphthalene (strong acid sites), respectively.